2019
DOI: 10.1017/sus.2018.16
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling urban data science for global climate solutions

Abstract: Non-technical summaryManhattan, Berlin and New Delhi all need to take action to adapt to climate change and to reduce greenhouse gas emissions. While case studies on these cities provide valuable insights, comparability and scalability remain sidelined. It is therefore timely to review the state-of-the-art in data infrastructures, including earth observations, social media data, and how they could be better integrated to advance climate change science in cities and urban areas. We present three routes for expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 214 publications
(304 reference statements)
0
52
0
Order By: Relevance
“…There is a scientific consensus on the need for spatially detailed information on urban landscapes at a global scale to support a range of environmental services 1 . The consensus has emerged as the simulation and forecasting capabilities of models have improved radically over the last decade and the demand for reliable urban-scale information that can inform policies has increased 2 .…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…There is a scientific consensus on the need for spatially detailed information on urban landscapes at a global scale to support a range of environmental services 1 . The consensus has emerged as the simulation and forecasting capabilities of models have improved radically over the last decade and the demand for reliable urban-scale information that can inform policies has increased 2 .…”
Section: Background and Summarymentioning
confidence: 99%
“…green fraction) and function (e.g. transportation networks) to mitigate the urban impact 1 , 21 23 . While these data can be assembled for data-rich cities, the challenge is to acquire sufficient information at very large scales using a consistent methodology.…”
Section: Background and Summarymentioning
confidence: 99%
“…In addition, this study cross-references the observed land-cover and land-use changes with historic and present-day planning policies. Considering the rapidly growing number of applications using the LCZ scheme [28] and the need for data-based approaches to upscale urban climate solutions [27] and integrated urban weather, environment and climate services [42], this effort is undertaken to demonstrate that the LCZ framework might push the mission of WUDAPT well beyond the provision of "urban canopy information and modelling infrastructure to facilitate urban-focused climate, weather, air-quality and energy-use modelling application studies" [28]. It provides a powerful means to transfer and translate scientific urban climate information to city practitioners, allowing them to form rational urban planning strategies toward the sustainable development of cities [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…by modifying the route network and allocate bus priority corridors. Through the use of big data curated towards transportation and tourism, we are able to understand how public transport is used at destinations, the precise distinction between urban and rural geographical spaces so as to transform public transport into a potential alternative model for travelling [67]. Socially, there also needs to be an understanding of the most important factors influencing tourist choices and satisfaction with public transport, and therefore, we can best encourage public transport use in tourism.…”
Section: Policy Implications For Local Decision-makersmentioning
confidence: 99%